Impacts of Cluster Frontline Demonstrations on Yield and Economics of Blackgram in Southern Part of Tamilnadu, India - B. Venudevan; Chelvi Ramessh; S. Krishnakumar; K. Krishnasurendar; A. Sheeba; Zadda Kavitha; B. Nallakurumban; J. Kannan (Archives of Current Research International, 2025)
Cluster Frontline Demonstrations were laid out to upscale improved technologies for enhancing the productivity of blackgram during rabi 2022-23 & 2023-24 by Krishi Vigyan Kendra, Virudhunagr, Tamil Nadu (India). One hundred and fifty demonstrations were conducted in 60 ha with the active participation of the farmers. The results of the demonstrations revealed that the average yield of blackgram under improved technology ranged from 8.4 to 8.6 q/ha with a mean of 8.5 q/ha; which was 25 per cent higher as compared to farmer’s practices (6.4 q/ha). The study exhibited reduced mean extension gap (2.32 q/ha) and technology gap (5.07 q/ha) with lower technology index (42.58 %) due to the higher yield realized in VBN 11 demonstration plots. The average mean net return (Rs. 38049.5/ha) and mean B: C ratios (2.09) were higher in improved technologies than the farmers’ practices (Rs.21282.5/ha) and mean B: C ratio (1.57). The present study resulted in substantial increase in productivity and returns to the farming community through the adoption of improved technologies.